Adsorption of Cations from a Cement Suspension onto Lignocellulosic Substrates and its Influence on Cement Setting - Pereira, C.; Caldeira Jorge, F.; Ferreira, J. M. F. (Journal of Wood Chemistry and Technology, 2005)
Abstract The calcium (Ca), sodium (Na), and potassium (K) contents of blue gum, maritime pine, and cork increased after these lignocellulosics were stirred with the filtrate of a cement suspension or a solution of calcium hydroxide. The adsorbed cations could be released easily by treatment with an acidic solution. It is suggested that those raw materials, and lignocellulosics in general, act as cation exchange substrates when they are mixed with cement and water to make wood?cement composites. The implications that such phenomena may have on cement hardening reactions, and how they could hinder them are discussed. The possibility that the phenomenon is related to well?known compatibility problems that many woods present when manufacturing wood?cement composites is discussed.
doi: 10.1080/02773810500366672doi: 10.1080/02773810500366672The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Adsorption; cations; cement; hindrance; interactions; lignocellulosics